Explaining the Recent Behavior of Inflation and Unemployment in the United States - Hogan, Vincent (Washington, D.C. : International Monetary Fund, 1998)
Low rates of inflation have been recorded in recent years, despite a decline in the unemployment rate. This phenomenon could be the result of a series of transitory shocks or of a permanent change in the structure of the economy leading to a lower NAIRU. The paper suggests that, while the NAIRU may have fallen slightly, it has not fallen by an amount sufficient to explain the recent behavior of inflation. A leading explanation for recent inflation performance appears to be favorable price shocks; in particular, the cost of imports has fallen sharply as the dollar has appreciated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet